A noninterventional observational registry of patients with multiple myeloma treated with lenalidomide in Taiwan - Shang-Yi Huang; Yuan-Bin Yu; Su-Peng Yeh; Tsai-Yun Chen; Woei-Yau Kao; Chih-Cheng Chen; Ming-Chung Wang; Hsuan-Yu Lin; Sheng-Fung Lin; Tseng-Hsi Lin; Ye Hua; Marie Puccio-Pick; et al. (Journal of the Formosan Medical Association, 2017)
The incidence of multiple myeloma in Asia has risen in the past 30 years. Lenalidomide, an IMiD immunomodulatory agent, has improved the overall survival in patients with relapsed/refractory multiple myeloma (RRMM) when used with dexamethasone versus dexamethasone alone. This observational registry (T-CC-MM-009; NCT01752075) assessed the safety and efficacy of lenalidomide plus dexamethasone in a large Chinese population of patients with RRMM. Methods: This registry followed the first 100 patients treated with lenalidomide plus dexamethasone in Taiwan. Patients were ≥18 years old and had ≥1 prior treatment. The recommended starting dose for the first four 28-day cycles was 25 mg lenalidomide on days 1–21 and 40 mg dexamethasone on days 1–4, 9–12, and 17–20. Thereafter, dexamethasone was given on days 1–4 only. The primary objective was safety; secondary objectives were efficacy, lenalidomide dosage, and reasons for discontinuation. Results: The median duration of treatment was 34.6 weeks, and 75.5% completed ≥3 cycles. Most patients (82.7%) experienced ≥1 treatment-related adverse event; the most commonly reported were neutropenia (23.5%), thrombocytopenia (19.4%), anemia (16.3%), fatigue (16.3%), and hypoesthesia (15.3%). Bleeding events (25.5% of patients) were mostly grade 1/2 (80%). Three patients (3%) had venous thromboembolic events. Two invasive second primary malignancies were reported; however, time to onset was <1 year, suggesting they may not be related to lenalidomide. The overall response rate was 34.7%; median time to disease progression was 20.5 months. Conclusion: These data confirm the safety and efficacy of lenalidomide plus dexamethasone for patients with RRMM in Taiwan.